2004
DOI: 10.1126/science.1101092
|View full text |Cite
|
Sign up to set email alerts
|

A Link Between mRNA Turnover and RNA Interference in Arabidopsis

Abstract: In RNA interference (RNAi), double-stranded RNA (dsRNA) triggers degradation of homologous messenger RNA. In many organisms, RNA-dependent RNA polymerase (RdRp) is required to initiate or amplify RNAi, but the substrate for dsRNA synthesis in vivo is not known. Here, we show that RdRp-dependent transgene silencing in Arabidopsis was caused by mutation of XRN4, which is a ribonuclease (RNase) implicated in mRNA turnover by means of decapping and 5'-3' exonucleolysis. When both XRN4 and the RdRp were mutated, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
269
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(282 citation statements)
references
References 27 publications
9
269
0
4
Order By: Relevance
“…This is also consistent with AGO4's capacity to slice RNA (15), and decapped RNA serving as a substrate for RDR6 to induce RNA silencing (37). In this scenario, the Pol IVa-RDR2-DCL3-AGO4 pathway precedes the RDR6/DCL4 production of 21-nt siRNAs, and provides the prediction that 24-nt but not 21-nt siRNAs, should be present in rdr6 scions grafted on S2 rootstocks.…”
Section: Nuclear Gene Silencing Directs Reception Of Mrna Silencing Isupporting
confidence: 56%
See 1 more Smart Citation
“…This is also consistent with AGO4's capacity to slice RNA (15), and decapped RNA serving as a substrate for RDR6 to induce RNA silencing (37). In this scenario, the Pol IVa-RDR2-DCL3-AGO4 pathway precedes the RDR6/DCL4 production of 21-nt siRNAs, and provides the prediction that 24-nt but not 21-nt siRNAs, should be present in rdr6 scions grafted on S2 rootstocks.…”
Section: Nuclear Gene Silencing Directs Reception Of Mrna Silencing Isupporting
confidence: 56%
“…The presence of only P-specific siRNAs in S1-or S2-silenced scions (Fig. 1c) suggests that the initiation of silencing via the Pol IVa-RDR2-DCL3-AGO4 pathway could result in the production of a decapped RNA substrate (37)(38)(39) for the amplification of P-specific dsRNA. In an effort to identify decapped RNAs, we performed 5Ј-RACE on RNA extracted from S2-silenced scions (Fig.…”
Section: Nuclear Gene Silencing Directs Reception Of Mrna Silencing Imentioning
confidence: 99%
“…In animals, some of these complexes are associated with components of the RNA silencing machinery (Leung et al, 2006), and there is evidence that Drosophila P-bodies are involved in miRNA-directed target decay through deadenylation and decapping, whereas translational repression is P-body independent (Eulalio et al, 2007). In plants, components of the RNA decapping machinery were found involved in RNA silencing (Gazzani et al, 2004;Gy et al, 2007), and the existence of P-bodies was recently demonstrated (Xu et al, 2006). Thus, it will be interesting to investigate which type of proteins, such as other members of the large AGO family, are linked to miRNAs and their mRNA targets in nonpolysomal fractions.…”
Section: Discussionmentioning
confidence: 99%
“…In general, uncapped fragments derived from mRNAs in eukaryotic transcriptomes are generated by decapping or endonucleolytic cleavage, and these RNA fragments are then rapidly recognized and degraded by 59 to 39 (e.g., XRN4) (Gazzani et al, 2004) and 39 to 59 (e.g., exosome) (Chekanova et al, 2007) exonucleases. Thus, they represent the degrading fraction of the transcriptome.…”
Section: Resultsmentioning
confidence: 99%